Managing Medical Records in Specialist Medical Centres - Md Zali, Mastura; Farik Mat Yatin, Saiful; Razilan Abdul Kadir, Mohd; Noraini Mohd Tobi, Siti; Hanis Kamarudin, Nurul; Nurul Emyliana Nik Ramlee, Nik (International Journal of Engineering and Technology, 2018)
A collection of facts about a patient’s life and health history of past and present illnesses and treatments is known as medical records. The health professionals were contributing to record the patient’s care. The responsibility in managing daily records that produced by each of department is by the Medical Records Department. It is a department under clinical support services with activities including managing of patient records, patient information production, management of medical reports, and hospital statistics. This article aims to discuss the challenge associated with managing medical records in the organization and how to handle and manage it with the records management as a tool to mitigate risk. Therefore, it is likely to prompt further research by addressing existing gaps towards improving service delivery that can contribute to the body of knowledge in the field of records management and archives generally.